Portable heart rate measurement through fingertip - Abd Jalil, Amirun Murtaza; Mohd Nur Izham, Umair (2016)
The main purpose of this project is to design and understand the portable heart rate measurement through fingertip and also observe how does the infrared sensor (IR) work. This project uses infrared sensor (IR) to sense the heart rate or number of heartbeats per unit of time through fingertip. Plus, it is assembled and represented in a model type Programmable Interface Controls (PIC). PIC can only uses if PIC has suitable code to run the circuit. This output of this project is based on pulses that can be counted segment display. By knowing the heart rate measurement, people can analyse themselves weather their own cardiovascular system level in good condition or not. The objectives of this project are to design simple medical check up using portable heart rate measurement and to analyse their own cardiovascular system level. Most of people nowadays and lead to the people that are not very concern on their own health. Based on the experts, everyone must do the medical check up at least two times a year. But, regard to the busy lifestyle they do not have time to do it. To overcome this problem, this project have been construct and built to demonstrates a technique to measure the heart rate by sensing the change in blood volume in a finger artery while the heart is pumping the blood. From this project, Infrared sensor (IR), Light Emmiting Diode (LED) and SSD is used to show the output of the heart rate measurement . LED will light up and blinking when the push start button is pushed and fingertip is replace at the finger place at the IR sensor and then it display on the SSD.